Determines factors of cultural city brand equity: from the perspective of a city’s integration with residents - Zhao, Wenqiang; Seokhyun, Lee (Journal of Asian architecture and building engineering, 2024)
The city brand, a vital strategic asset, leverages a city’s unique qualities to enhance attractiveness, with a rising interest in using the cultural city as a distinct brand type. Residents, as the most significant stakeholders, play a crucial role in promoting the city’s image and branding. This study aims to investigate the relationship between city image, city attachment, city ambassador behavior, cultural city brand equity, and quality of life. We conducted an online survey of Chengdu residents, analyzed 355 valid responses, and tested hypotheses using structural equation modeling. Results indicate that city image, residents’ city attachment, and city ambassador behavior have a significant positive impact on cultural city brand equity, with standardized path coefficient values of 0.277, 0.224, and 0.271, respectively. In terms of quality of life, both city image and brand equity make substantial contributions, where significance is p < 0.001. City image is an antecedent of city attachment and ambassador behavior with standardized path coefficient values of 0.288 and 0.235, respectively. The research implications provide empirical evidence for the brand equity literature in the context of cultural city, which not only enriches the connotation of brand equity theory, but also clarifies the key role of residents in city branding.